Visual instrumentation optical design and engineering principles - Mouroulis, Pantazis (McGraw-Hill handbooks, 1999)
The tools you need for visual instrument design are here: Visual Instrumentation: Optical Design and Engineering Principles details design techniques beginning with the eye itself. Authored by a team of top experts in the field, this groundbreaking, state-of-the-art volume provides the information needed to design and evaluate optical instruments. Whether you're an optical engineer, lens designer, optical technician, or vision professional, Visual Instrumentation makes understanding, designing, and evaluating visual instruments clearer and easier. Packed with over 150 concept-clarifying illustrations, this book gives a highly instructive, detailed look at: eye characteristics and behavior; aberrations and image quality in the human eye; modeling of the eye's refractive and neurosensor systems; image quality assessment and optimization; design considerations for binocular head-mounted displays; basic lense design for instrumentation; applications of diffractive optics; testing methods for visual instruments; and more.